COMPARISON OF PLACENTAL WEIGHT IN PREGNANCIES WITH STILLBIRTH AND LIVE BIRTH CONTROLS - Muttaqui, Midhat; Usman, Nema; Zaidi, M Tariq; Khan, Tamkin; Afroz, Nishat (International Journal of Human and Health Sciences (IJHHS), 2023)
Introduction: A foetus born after 20 weeks of gestation that shows no signs of life on direct observation or a zero Apgar score at 1 and 5 minutes defines stillbirth. It can be due to maternal, foetal, or placental causes. According to WHO, annually about 2 million stillbirths occurs Placenta being a multitalented organ alone fulfils the nutritive, respiratory, excretory functions during intrauterine life The ability of foetus to grow in uterus depends on the placental perfusion. Weight of placenta is a measure of its function. The ratio between weight of placenta and neonatal weight is 1:6. at term. Material and Methods: This study was conducted on 100 pregnant women with stillbirth and on 100 pregnant women with live birth. The placentas were taken from the Department of Obstetrics and Gynecology, JNMC, and weighed. Results: Median (25th-75th percentile) of placental weight (gm) in cases was 355(285.25-480) which was significantly lower as compared to controls [460(387.5-502.5)]. (p value <.0001; Odds ratio (95% CI): -0.994(0.991 to 0.997. Conclusion(s): With the increase in placental weight, risk of still birth significantly decreases with adjusted odds ratio of 0. 993.Low Placental weight is a cause of still births. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S62-S68